Meanings of happiness among two ethnic groups living with advanced cancer in south London: a qualitative study. Issue 5 (28th May 2012) - Koffman, Jonathan; Morgan, Myfanwy; Edmonds, Polly; Speck, Peter; Siegert, Richard; Higginson, Irene J.
Abstract Objective Happiness is a central component in quality of life but little is known about its meanings among people living with an advanced disease and those from diverse communities. This study explores and compares, for the first time, the centrality and interpretations of happiness across two cultural groups living with advanced cancer. Methods Semi‐structured interviews among 26 Black Caribbean and 19 White British cancer patients were conducted in hospital and home settings. Results Thirty eight participants volunteered views on happiness, which were related to four main themes: empty lives, a theme associated with lives devoid of contentment; happiness and the physical form principally, associated with the absence of distressing symptoms; 'love and affection' associated with family and friends; and 'realising personal meaning in life', most common among the Black Caribbean participants and related to God, prayer and the sacred world. The presence of cancer pain even when refractory did not preclude manifestations of happiness in this domain. Conclusions We identified that happiness was central to many patients' quality of life during advanced cancer. Moreover, happiness was multidimensional and at times culturally patterned. We recommend that health and social care professionals increase their awareness and skills‐set in relation to exploring happiness. Further, we recommend greater efforts are invested in cultural relativism to service the physical, psychological, social and spiritual issues that contribute towards moments of happiness among diverse communities. Copyright © 2012 John Wiley & Sons, Ltd.